(untitled) (Al-Qamar, 2021)
Signification of method and style cannot be denied in composition and compilation as it is the writing style of the writer which motivates the reader not only to read but also to memorize the text. Method is the standard judge and appraise the aptitude of a writer. It is not overstating to say that Allama Shiblī Nuʻmānī was a writer and researcher of sublime class. “Sīrat-un-Nabī” is speaking proof of his fantastic research quality as it is in perpetual determination to guide the sentient readers by illuminating the knowledge zones. Allama Shibli has composed the facts and figures in such a symmetric way which bestows “Sīrat-un-Nabī” with a prominent position among the other seat books of urdu. He specially described the Holy wars of Prophet (PBUH) in an inquisitive manner. His writing style has made the circumstances of the Holy wars sequential and full of excitement. He has not only described the circumstances of the Holy wars in detail but also answered the objections of orientalists and critics reasonably. Moreover, causes and motives of the Holy wars has also been clarified. His very this method makes him distinguished amid other seat writers. In this article, the personality of Allama Shibli Nomani, the brief introduction of his book “Sīrat-un-Nabī (SAW)” and the method of description of the Holy wars of the Holy Prophet (PBUH) have been discussed so that his writing style may be manifested for the readers. Keywords: Method and style, Allama Shibli Nomani, Sīrat-un-Nabī, Holy wars of the Holy Prophet (PBUH).